Ethnomedicinal understandings and pharmacognosy of Dischidia (Apocynaceae: Asclepiadoideae): A potential epiphytic genus - Gitartha Saikia; Nilakshee Devi (Phytomedicine Plus)
Background: This is a comprehensive review on the epiphytic genus Dischidia of Apocynaceae s.l. with pivotal role in their folk medicinal practices and further investigating the secondary metabolites involved in curing various diseases via traditional means. Purpose: The present study focused on the traditional medicinal uses of the genus Dischidia in different corners of the world by diverse indigenous peoples to reflect a lucid image regarding the traditional and ethno pharmacological significance of the genus and their continuous considerable services for the wellbeing of the people from the primordial period to the present era. Methods: Different ethnomedicinal practices of the genus, plant parts used, modes of their administrations, types of diseases cured, reported chemical constituents and their therapeutic activities against a particular type of illness were analyzed based on the previously documented literatures and thus scrutinized the medicinal prospects of the genus for the forthcoming generation. Results: The present review reports the utilization of 10 species of Dischida across eight countries of the world in the field of folk medicines. Till hitherto, 21 bioactive compounds have been isolated from four species of Dischidia. The therapeutic potentialities of the documented bioactive compounds are boon with 18 different kinds of healing activities with the discovery of novel chemical compounds makes Dischidia as a potential and promising epiphytic genus of the Plant Kingdom.